Lunturnya Pendidikan Keluarga dalam Novel ABG Karya J.M.V Sunarjo (Kajian Sosiologi Sastra) - Rosiatima, Rosiatima; Darni, Darni (Universitas Negeri Surabaya, 2023)
ABSTRACT Education in the family affects all children's behavior, because education is the first and foremost education. The fading of family education can trigger the moral decline of the nation's children. Currently there are still many family problems that directly affect the growth and development of children. The role of parents is very important to create maximum family education. The ABG novel by J.M.V Sunarjo is a literary work that explains family education and its problems in accordance with the conditions of society. This research will discuss: (1) The causes of the fading of family education and (2) How to resolve the fading of family education. This study was analyzed using a sociology of literature study by Wellek and Warren. The research method used is descriptive qualitative. The primary data source in this research is from the ABG Novel by J.M.V Sunarjo, while the secondary data is in the form of books, articles, theses, etc. Research data is obtained from sentences, words, and dialogues that have something to do with the topic being discussed. Data collection techniques using literature study techniques, recording and classifying data in research objects. Data analysis techniques, namely data reduction, data presentation, and draw conclusions by descriptive or explaining. The results of this study are the causes of the fading of family education, namely the actions of emban cindhe emban siladan, family disharmony, and lack of attention to children. Meanwhile, the solution to solving this problem is to act fairly and pay attention to children. Keywords: Education, Family, and Children. ABSTRAK Pendidikan dalam keluarga mempengaruhi segala tingkah laku anak, karena pendidikan tersebut merupakan pendidikan yang pertama dan utama. Lunturnya pendidikan keluarga dapat memicu kemerosotan moral anak bangsa. Saat ini masih banyak permasalahan keluarga yang berpengaruh langsung pada tumbuh kembang anak. Peran orang tua sangat penting untuk menciptakan pendidikan keluarga yang maksimal. Novel ABG karya J.M.V Sunarjo adalah salah satu karya sastra yang menjelaskan tentang pendidikan keluarga dan permasalahannya sesuai dengan kondisi masyarakat. Penelitian ini akan membahas: (1) Penyebab lunturnya pendidikan keluarga dan (2) Cara menyelesaikan lunturnya pendidikan keluarga. Penelitian ini dianalisis menggunakan kajian sosiologi sastra oleh Wellek dan Warren. Metode penelitian yang digunakan adalah deskriptif kualitatif. Sumber data primer dalam penelitian dari Novel ABG karya J.M.V Sunarjo, sedangkan data sekunder berupa buku, artikel, skripsi, dll. Data penelitian diperoleh dari kalimat, kata-kata, dan dialog yang ada hubungannya dengan topik yang dibahas. Teknik pengumpulan data menggunakan teknik studi pustaka, mencatat dan mengklasifikasi data dalam objek penelitian. Teknik analisis data yaitu reduksi data, penyajian data, dan menarik kesimpulan dengan cara deskriptif atau menjelaskan. Hasil penelitian ini adalah penyebab lunturnya pendidikan keluarga ada tindakan emban cindhe emban siladan, disharmonisasi keluarga, dan kurangnya perhatian kepada anak. Sedangkan solusi untuk menyelesaikan masalah tersebut adalah bertindak adil dan memberi perhatian kepada anak. Kata Kunci: Pendidikan, Keluarga, dan Anak.